TEATER TUTUR BAPANDUNG DALAM MASYARAKAT BANJAR - NFN Saefudin (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2019)
The problem discusses in this study is how does the form of narrative theater bapandung (monologue) in Banjar society. The aim of this study is to reveal the form of narrative theater bapandung (monologue) in Banjar society. Banjar society in South Kalimantan has lots of oral traditions, one of them is narrative theater bapandung. A man  is called story teller because of his cleverness telling a story in monologue way and playing several characters, that man is called pamandungan. The story in bapandung has lots of jokes played by pamandungan or the performance player. This study uses descriptive qualitative method. It is a method to get information about narrative theater bapandung in Banjar society deeply. The result shows about the description of narrative theater bapandung in Banjar society.